Optimizing Students' Interest in Learning and Mastery of Arabic Vocabulary Through the Use of Interactive Games Gimkit - Assyfa Dwi Utami; Ahmad Maghfurin (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study investigates the effectiveness of Gimkit, an innovative gamified learning platform, in enhancing students’ interest and vocabulary mastery in Arabic at MTs Sadamiyyah Jepara. The purpose of this study is to see the impact of Gimkit on students' interest and mastery of vocabulary in Arabic at MTs Sadamiyyah Jepara. The research employs a classroom action research (CAR) approach, conducted in two cycles, with data gathered through observation, questionnaires, interviews, and vocabulary tests. Findings indicate that Gimkit significantly boosted student engagement, motivation, and vocabulary retention by transforming traditional Arabic learning into an interactive and enjoyable experience. The platform’s unique features, such as real-time quizzes, competitive games, and reward systems, created a dynamic learning environment that addressed common challenges, including low motivation and difficulty in memorizing vocabulary. Adjustments made during the intervention, such as customizing vocabulary sets and incorporating collaborative activities, further optimized student performance. This study underscores the potential of gamification as a transformative tool in Arabic language education, offering practical insights into how technology can foster greater participation, improve linguistic competence, and promote positive learning attitudes in Islamic educational settings.